PERBEDAAN pH SALIVA ANTARA BERKUMUR INFUSED WATER LEMON DAN INFUSED WATER STROBERI PADA PENGHUNI ASRAMA GRIYA BHAKTI HUSADA SEMARANG - Sadimin Sadimin; Irmanita Wiradona (Jurnal Kesehatan Gigi, 2016)
ABSTRACT       The degree of acidity of pH saliva is a way to measure the degree of acid or alkaline of the saliva liquid. Gargling is the simple way to maintain the cleanliness of the teeth and the mouth.the fruits which contain of sour taste are chosen, strawberry and lemon fruits are chosen than any other fruits because they contain sour taste and produce fresh taste. They can use to make infused water. The objectives of this research are to determine the alteration of pH saliva before and after given treatment or gargling using strawberry and lemon infused water.       The researcher used Quasi Experimental or Experimental Pseudo Method. The researcher used pretest and posttest in the research design. The researcher divided two group designs. Both of them were given the same treatment by measuring the pH saliva before and after giving treatment. The sample of lemon infused water are 40 and the strawberry are also 40, so the total of the sample are 80 responden. Data analysis uses independent frequency and statistical distribusi of t-test.       The result of the research are about the difference of pH saliva before and after given the treatment using lemon and strawberry infused water. The difference of average of pH saliva before anf after given the treatment using lemon infused water is 0,3. Then, the difference of average of pH saliva before and after given the treatment using strawberry infused water is 0,4. In conclusion, both of them are equally can recude pH saliva, but using strawberry infused water work much better than lemon. The need to do more of this research is using different fruit, such as grape, kiwi, and star fruit.Keywords : The degree of acidity of PH saliva, Lemon and Strawberry infused water